Speed control for K-mirror of 2-m telescope using improved active disturbance rejection controller. (December 2018) - Deng, Yongting; Xia, Peipei; Li, Hongwen; Wang, Xianjun
Highlights: An extended state observer is designed to estimate the external disturbance. The larger P-type gain can solve the problem of "controlling small dead zone". The smaller P-type gain can solve the problem of "controlling large overshoot". The proposed strategy gets better control performance and anti-disturbance ability. Abstract: To meet the high-precision requirements of the speed control system of the K-mirror of a 2-m telescope in terms of fast response, small overshoot, and strong anti-disturbance ability, a new active disturbance rejection controller (ADRC) based on the adaptive control law parameter is proposed. On the basis of the field rotation angle of the altitude-azimuth (alt-az) telescope and speed control performance requirements of the K-mirror turntable, an extended state observer is employed to estimate disturbances accurately from the input and output information of the system response. Then, the estimated values are used by the output side of the speed controller as a feed-forward compensation to eliminate the effects of the disturbances. However, the response of the turntable is slow when the speed is sufficiently low and its overshoot is large when the speed is sufficiently high. Thus, the performance of the K-mirror servo system is degraded and the high-precision requirements are not satisfied. Therefore, this paper proposes an adaptive scheme developed by designing the P-type gain of the feedback control law into a function, which can be automatically adjusted with a change in the system input speed. When the turntable of the K-mirror runs at a low speed, the proposed method produces a large P-type gain to accelerate the system's speed response. When the turntable runs at a high speed, the method suppresses the P-type gain and guarantees that the system has no overshoot. Experiments are conducted using a digital signal processor and a field-programmable gate array (FPGA)-based platform. The results show that the adaptive scheme fulfills the system requirements with the fastest speed response, minimizes the overshoot, and exhibits satisfactory anti-disturbance performance compared to the proportional-integral (PI) controller and ADRC.